Guns, Thorns, and Zeal: Popular Depictions of a Kombative Christ - Chavez, William S. (Religions, 2024)
What are the political, gender, and theological implications at stake when associating Jesus with modern combat and righteous violence? Jesus is rendered in combative form across media—i.e., live-action films and shorts, animated television, sketch comedy, graphic novels, and video games. This rendition occurs at a confluence of meaning, most immediately for the sake of generating comedy through juxtaposition (in this case, rendering the meek with a sword) and/or reaffirming Jesus’ prominent cultural value through an association with other popularly mediatized entities. Beyond these initial layers of significance, however, I argue that Jesus becomes associated with violence and brutality for the sake of de/legitimizing politically conservative ideologies with respect to Christianity and American exceptionalism, redeeming the crisis of “domesticated masculinity” and fortifying traditional masculine norms, and theologically reinstituting popular paradigms of low Christology. Ideological “manhood” remains traced to one’s ability to perform traditional gender roles (i.e., family provider, community protector, and father/procreator). To capture the discrepancy that Jesus of Nazareth, as presented in canonical gospels, largely concerns none of these roles, I analyze the hypermasculine Christ, and the various weapons he employs, as part of a popular genealogy of Western value systems and discourse. Though in this article I reference some examples of non-American media, I reserve my analysis and commentary for the stakes and implications of what it means for U.S. Americans to produce and consume such content. In short, I submit that popular America idolizes itself in the form—one amidst many—of a naïve, combative, and boorish Christ: an arrogant and, at times, narcissistic man with delusional views of the world made dangerous through invasive power and authority. Western entertainment has deemed the United States (through its fictional stand-ins) as morally failing yet still chosen. Within this logic, American Christians need not reform their ways as long as they cultivate evidence of their exceptionalism.